Time Trends in Race-Ethnic Differences in Do-Not-Resuscitate Orders After Stroke - Bailoor, Kunal (Stroke, 2019)
BACKGROUND AND PURPOSE: Do-not-resuscitate (DNR) orders are common after stroke, though there are limited data on trends over time. We investigated time trends in DNR orders in a community with a large minority population. METHODS: Cases of ischemic stroke (IS) or intracerebral hemorrhage (ICH) were identified from the Brain Attack Surveillance in Corpus Christi (BASIC) study from June 2007 through October 2016. Cox proportional hazards models were used to assess time to DNR orders, with an interaction term added to allow separate hazard ratios for early (≤24 hours) and late (>24 hours) DNR. Stroke-type specific calendar trends were assessed with an interaction term between calendar year (linear) and stroke type. RESULTS: 2,672 cases were included (ICH 14%). Mean age was 69, 50% were female, and race-ethnicity was Mexican American (MA, 58%), non-Hispanic White (NHW, 37%), and African American (AA, 5%). Overall, 16% had a DNR order during the hospitalization. For ICH, DNR orders (early and late) were stable over the study period. However, early DNR orders became more common over time after IS (hazard ratio for 2016 vs 2007: 1.89, 95% CI 1.06, 3.39), with no change over time for late DNR orders after IS. MAs (HR 0.65, 95% CI 0.50, 0.86) and AAs (HR 0.17, 95% CI 0.04, 0.71) were less likely than NHWs to have early DNR orders, though there were no race-ethnic differences in late DNR orders. There was no change in race-ethnic difference in DNR orders over the time of the study (interaction p > 0.60). CONCLUSIONS: Despite revised national guidelines cautioning against early DNR orders in ICH, presence of DNR orders after ICH was stable between 2007 and 2016, with only slight increases in early DNR orders after IS. MAs and AAs remain less likely than NHWs to have early DNR orders after stroke.